2022
DOI: 10.1016/j.ekir.2022.01.1064
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Hematopoiesis of Indeterminate Potential and Diabetic Kidney Disease: A Nested Case-Control Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
10
1
Order By: Relevance
“…By our estimation, 40 of the 127 variants reported by Denicolò et al. 1 would not be considered CHIP driver variants using the cited conventional criteria. 3 , 4 , 5 Inclusion of benign or misclassified variants would increase CHIP prevalence but may bias results toward the null hypothesis because they would be expected to be evenly represented across groups.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…By our estimation, 40 of the 127 variants reported by Denicolò et al. 1 would not be considered CHIP driver variants using the cited conventional criteria. 3 , 4 , 5 Inclusion of benign or misclassified variants would increase CHIP prevalence but may bias results toward the null hypothesis because they would be expected to be evenly represented across groups.…”
mentioning
confidence: 73%
“…To the Editor: We read the work of Denicolò et al 1 with great interest, reporting a lack of association between clonal hematopoiesis of indeterminate potential (CHIP) and incident or progressive diabetic kidney disease published in KI Reports. A major challenge when investigating CHIP is variant interpretation.…”
mentioning
confidence: 99%
“…One reasonable explanation was that more small-clone mutations within these genes could be detected in our study (76% for BCORL1 , 77% for SE TD2 ), which would be missed by low-depth sequencing. Actually, BCORL1 has been most frequently identified by previous high-depth sequencing studies . In addition, ethnic heterogeneity may contribute to the disparities in CHIP profile .…”
Section: Discussionmentioning
confidence: 99%
“…Large population studies have also found higher rates of diabetes mellitus type 2 in patients with CH [15]. Investigation into the incidence or progression of diabetic kidney disease have not found an association with CH but there is evidence that CH promotes the development of chronic kidney disease at large, especially in the context of myeloid CH mutations and myeloid mCAs [75,76]. Thus, aggravation of cardiac risk factors like diabetes and chronic kidney disease is an additional mechanism through which CH mutations are able to impact cardiovascular outcomes.…”
Section: Molecular Mechanisms Of Ch-mediated Cardiotoxicitymentioning
confidence: 99%